TANGGUNG GUGAT RUMAH SAKIT BM DAN TIM DOKTER ATAS TINDAKAN PEMBIUSAN TOTAL DI PERGELANGAN TANGAN TN YANG BERAKIBAT SYARAF JARINGAN TANGAN MATI DAN MEMBUSUK SEHINGGA DUA JARI HARUS DIAMPUTASI - Stevie Maggie Santoso (Jurnal HUKUM BISNIS, 2018)
When a person needs a medical action the person will go to the hospital or the doctor's office to ask for help in handling the health constraints he is facing. But if such medical action harms the patient for any mistakes, omissions or lack of prudence, then the need to provide legal protection against the patient who loses the medical treatment. The results of the study show BM Hospital and the team of doctors accountable to the TN, because: BM Hospital is legally responsible for all losses caused by negligence made by health personnel, ie doctors working in the hospital, based on Article 46 of the House Law Pain and Article 1367 KUHPer. The team of BM Hospital physicians is legally responsible for providing four injections of anesthesia that are not in accordance with professional standards, standard operating procedures, and not referring patients to other doctors who have better skills or abilities, pursuant to Article 51 of the Medical Practice Law.Keywords: Liability, Hospital, Medical Actions